Political Institutions and Macroeconomic Factors as Determinants of Credit Risk in South Africa - Zhou, S.; Tewari, D.D (Journal of Economics and Behavioral Studies, 2018)
This study analyses the effects of political institutions and macroeconomic factors on credit risk in South Africa using quarterly data between 1998 and 2016. The study uses the ARDL approach to cointegration and reports on both long-run and short-run influences of credit risk. In the long-run political institutions and gold prices are found to positively impact credit risk whereas Gross domestic product has a negative influence on credit risk. In the short-run however political institutions have a negative influence on credit risk. Further, the study confirms the recent country risk downgrades by rating agencies, S & P, Moody and Fitch. Policies that grow the economy and are consistent with the government’s long-term strategy needs to be followed to improve investor and lender confidence.